Increased interest and concentration of student learning with using the kotak pas - Siahaan, Doni Aldo; Nasution, Putri Khairiah; Hakim, Lukman (Talenta Publisher, 2020)
The learning model is one of the important parts in the world of education. Learning models with the involvement of play can help students understand mathematic and science. One method of play that can be used by elementary students is the Kotak Pas. Kotak Pas is a learning media that is easy to use, easy to carry or move to place. Kotak Pas is equipped with ten game books that contain mathematic and science. Each book has levels, from the easiest to the most difficult. Community service activities are carried out with several methods, namely conducting surveys and designing teaching materials, introducing Fitting Boxes, training teachers and students with Kotak Pas, and feedback.